The Dutch East India Company and the Chinese Tea Trade Before 1757 - Widaratih Kamiso (Universitas Gadjah Mada, 2012)
This article points out the development of the Dutch East India Company in China tea trade. As this article shows, the Dutch had the superior role to supply Asian product in Europe in the seventeenth century. They held the Spice Island in the archipelago. On the other hand the product from Spice Island was not so fashionable in the eighteenth century. The British took over a leading position in the world market by having a direct route to China. In Europe, China tea became popular. The Dutch wanted to compete with the British in tea trade. To explain the dynamics of the Dutch in China tea trade, the Chinese character became important to understand. The Dutch strategies to deal with the tea trade in China showed that they longed to get back to their glorious day in Europe as a leader.